Creating Methodological Capabilities Of Students On The Base Of Design Technologies In Higher Education Institutions - Almamatova Zebo (Zien Journals, 2024)
This article presents ideas on creating methodological opportunities for students based on design technologies in family educational institutions.
Keywords: Design; technology; methodology; interactive